Parathyroid Adenoma - The Leading Cause of Primary Hyperparathyroidism: Case Report - Martyna Zielnik; Julia Dubel; Szymon Kalinowski; Sabina Kadłubek; Patrycja Rembisz; Anna Czuba; Pola Knurowska; Klaudia Serafin; Aleksander Wrona; Aleksandra Słowikowska (Quality in Sport)
Primary hyperparathyroidism is an endocrine disorder characterized by excessive secretion of parathyroid hormone (PTH) by the parathyroid glands, disproportionate to the physiological requirement for calcium concentration. This hypersecretion of PTH occurs independently of dysregulation in calcium-phosphate metabolism. The predominant etiology of primary hyperparathyroidism is the presence of a parathyroid adenoma. (7)